The war : an intimate history, 1941-1945 - Ward, Geoffrey C.; Burns, Ken, 1953-; Novick, Lynn. (New York : A.A. Knopf, 2007)
As companion to the PBS series airing in September 2007, "The War" focuses on the citizens of four towns--Luverne, Minnesota; Sacramento, California; Waterbury, Connecticut; Mobile, Alabama, following more than forty people from 1941 to 1945. Maps and hundreds of photographs enrich this compelling, unflinching narrative.
A necessary war, December 1941-December 1942 -- When things get tough, January - November 1943 -- A deadly calling, November 1943-June 1944 -- Pride of our nation, June-August 1944 -- Fubar, August-December 1944 -- The ghost front, December 1944-March 1945 -- A world without war, March-August 1945.
Based on Burns' documentary, The war.
Includes bibliographical references (p. 436-449) and index.
Keywords: World War, 1939-1945 -- United States; World War, 1939-1945 -- Social aspects -- United States